Chest Radiography in Supporting the Diagnosis of Asthma in Children with Persistent Cough. Issue 2 (March 2014) - Halaby, Claudia; Feuerman, Martin; Barlev, Dan; Pirzada, Melodi
Abstract: Objective: To establish whether chest radiographic findings suggestive of lower airway obstruction (LAO) disease support the diagnosis of asthma in pediatric patients with persistent cough in an outpatient setting.Methods: 180 patient charts were reviewed. The patients were children aged 1 to 18 years referred over a 3–year period to a pediatric pulmonary subspecialty clinic for evaluation of cough lasting ≥ 4 weeks. Chest radiographic images obtained after the initial evaluation of 90 patients diagnosed with cough–variant asthma and 90 patients diagnosed with persistent cough from nonasthma origins were compared with radiologic findings of a control group consisting of patients with a positive tuberculin skin test and no respiratory symptoms. Increased peribronchial markings/peribronchial cuffing and hyperinflation were considered radiographically suggestive findings of LAO disease.Results: Children diagnosed with cough–variant asthma at the initial evaluation had higher rates of chest radiographic findings suggestive of LAO disease (30.00%) than children with persistent cough from other causes (17.80%) or those with a positive tuberculin skin test and no respiratory symptoms (8.16%) (overall P value = 0.0063). They also had higher rates of spirometry abnormalities suggestive of an LAO defect. Children with chest radiographic findings suggestive of LAO disease were found to be younger than those with normal chest radiographic findings (5.0 ± 2.7 years vs 8.6 ± 4.7 years; P < 0.0001).Conclusion: This study suggests that chest radiographic findings indicative of an LAO in correlation with the clinical presentation can support the diagnostic suspicion of asthma, especially in younger children unable to perform spirometry.